OVERVIEW OF CERVICAL CANCER IN BRAZIL: risk factors, prevention, and public health challenges (REMUNOM, 2026)
Cervical cancer (CC) persists as a relevant public health problem in Brazil, characterized by high incidence and mortality rates, especially in the North and Northeast regions. This narrative review aims to consolidate knowledge on the epidemiology, risk factors, and prevention strategies for CC in the Brazilian context. Persistent infection by the Human Papillomavirus (HPV) is the main etiological factor, with types 16 and 18 accounting for most cases. Carcinogenesis is a slow process, influenced by a complex interaction of infectious, behavioral, reproductive, and socioeconomic factors, such as coinfection with other STIs, early sexual initiation, multiparity, smoking, and low socioeconomic status. Control strategies are based on primary prevention, through HPV vaccination, and secondary prevention, through screening with the Papanicolaou test and, more recently, HPV-DNA tests. Despite the availability of effective tools, the effectiveness of prevention programs is limited by access barriers and low adherence, highlighting the need for public policies that address the social determinants of health to reduce inequalities and advance in the control of the disease.